2003
DOI: 10.1038/sj.bmt.1704145
|View full text |Cite
|
Sign up to set email alerts
|

Induction of oral tolerance in bone marrow transplantation recipients suppresses graft-versus-host disease in a semiallogeneic mouse model

Abstract: Summary:Graft-versus-host disease (GVHD) is the major obstacle for successful allogeneic stem cell transplantation (SCT). Morbidity and mortality are high, and novel therapeutic strategies are required. Current therapy, which is based mainly on immunosuppression, is associated with a high degree of complications. Immune hyporesponsiveness induced by oral antigen administration has recently been shown to prevent the development of chronic GVHD (cGVHD) in a murine model. The aim of the present study was to evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 24 publications
0
12
0
1
Order By: Relevance
“…38 While some authors have described a predominant inflammation of the colon in their experimental models, 39 others have reported inflammation of both the large and small bowel, 40 or mainly of the small bowel. 41 Differences were not only related to the experimental models used, they also varied between different investigators using the same donor and recipient strains. These differences imply that epigenetic factors such as housing conditions and in consequence differences in microbial colonization could have an influence on GVHD manifestation.…”
Section: Discussionmentioning
confidence: 99%
“…38 While some authors have described a predominant inflammation of the colon in their experimental models, 39 others have reported inflammation of both the large and small bowel, 40 or mainly of the small bowel. 41 Differences were not only related to the experimental models used, they also varied between different investigators using the same donor and recipient strains. These differences imply that epigenetic factors such as housing conditions and in consequence differences in microbial colonization could have an influence on GVHD manifestation.…”
Section: Discussionmentioning
confidence: 99%
“…Although promising, the clinical application of both protocols, oral tolerance induction (12) and probiotic treatment (30), cannot be used in transplanted patients. Once the conditioning regimen alters the intestinal epithelial barrier, these patients require special attention regarding their diet.…”
mentioning
confidence: 99%
“…Far from being just a matter of hyporesponsiveness, oral tolerance is an active immunologic event influenced by numerous factors such as Ag dose, microbiota, and costimulatory molecules, resulting from multiple mechanisms of action (6). Induction of oral tolerance has been shown to be effective in various experimental models of immune disorders (7)(8)(9) including GVHD (10)(11)(12). In fact, Nagler et al (12) demonstrated that it is possible to alleviate acute GVHD (aGVHD) severity by the induction of oral tolerance in the recipient, although the maintenance of the GVL effect was not addressed in that study.…”
mentioning
confidence: 99%
“…[17][18][19] Alternatively, restoring T cells after transplantation has been suggested as a valuable option to prevent the side effects of T cell depletion. 20 Other experimental approaches to reduce GVHD, such as induction of oral tolerance 21 or treatment with donor regulatory T cells, 22 dendritic cells 23 and NK cells, 24 are currently under investigation as well.…”
mentioning
confidence: 99%